2022
DOI: 10.1002/ejsp.2901
|View full text |Cite
|
Sign up to set email alerts
|

Cultural group norms for harmony explain the puzzling negative association between objective status and system justification in Asia

Abstract: Why do poorer and less educated Asians trust their institutions of governance more than their richer and well educated counterparts, despite their disadvantaged position within society? System justification theory (SJT) assumes that this trust is driven by a system‐level motivation that operates independently from social identity needs. In two nationally representative surveys spanning several years (Ntotal = 221,297), we compared SJT's explanation with a newer social identity model of system attitudes (SIMSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…Researchers who have defined status in subjective terms rarely find support for status‐legitimacy effects, while others who have used objective SES have found support (Brandt, 2013; Brandt et al, 2020, Davidai, 2018; Henry & Saul, 2006; Jost et al, 2003; Jost & Hunyady, 2005; Li, Wu, & Kou, 2020; Li, Yang, et al, 2020; Sengupta et al, 2015; Vargas‐Salfate et al, 2018; Whyte & Maocan, 2010; Yang et al, 2016; Zimmerman & Reyna, 2013). Three recent studies found evidence of status‐legitimacy effects when differentiating objective and subjective SES in both large cross‐cultural and single country tests (Kim et al 2022; Owuamalam et al, in press; Zhang et al, 2022). Consistent with our SIAM postulates, Owuamalam et al (in press) argue that cultural group norms surrounding social identity, such as the harmony creed, help to explain the relationship between objective SES and system justification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers who have defined status in subjective terms rarely find support for status‐legitimacy effects, while others who have used objective SES have found support (Brandt, 2013; Brandt et al, 2020, Davidai, 2018; Henry & Saul, 2006; Jost et al, 2003; Jost & Hunyady, 2005; Li, Wu, & Kou, 2020; Li, Yang, et al, 2020; Sengupta et al, 2015; Vargas‐Salfate et al, 2018; Whyte & Maocan, 2010; Yang et al, 2016; Zimmerman & Reyna, 2013). Three recent studies found evidence of status‐legitimacy effects when differentiating objective and subjective SES in both large cross‐cultural and single country tests (Kim et al 2022; Owuamalam et al, in press; Zhang et al, 2022). Consistent with our SIAM postulates, Owuamalam et al (in press) argue that cultural group norms surrounding social identity, such as the harmony creed, help to explain the relationship between objective SES and system justification.…”
Section: Discussionmentioning
confidence: 99%
“…Three recent studies found evidence of status‐legitimacy effects when differentiating objective and subjective SES in both large cross‐cultural and single country tests (Kim et al 2022; Owuamalam et al, in press; Zhang et al, 2022). Consistent with our SIAM postulates, Owuamalam et al (in press) argue that cultural group norms surrounding social identity, such as the harmony creed, help to explain the relationship between objective SES and system justification. In China, cultural norms create a sense of obligation (for low objective status individuals) to accept the hierarchical authority and the system—it is prudent to accept their disadvantaged position and acquiesce to the status quo.…”
Section: Discussionmentioning
confidence: 99%
“…Superordinate ingroup identification was operationalized as the extent to which women took pride in their nation, and was assessed with the item: "How proud are you to be [country's nationality inserted here]?" (see also Owuamalam et al, 2022). It is important to note that pride is one of the dimensions of group identification, specifically tapping its affective component (Ellemers et al, 1999;Leach et al, 2008).…”
Section: Predictorsmentioning
confidence: 99%
“…One limitation to Study 1 was that we measured system justification in terms of satisfaction and trust in government and national institutions. Although this measure has been routinely used to tap system justification across several studies (e.g., Caricati, 2017;Owuamalam et al, 2022;Szabó & Lönnqvist, 2021), skeptics might nonetheless question the extent to which the pattern of result on this measure extends to the more rountine measurements of system justification. Hence, we measured national system justification with eight items taken from the general system justification scale (Kay & Jost, 2003).…”
Section: Participantsmentioning
confidence: 99%
“…b. Several studies that have examined the existence of the system motive in large-scale nationally representative surveys have produced mixed evidence (e.g., Brandt, 2013;Buchel et al, 2020;Caricati, 2017;Henry & Saul, 2006;Jost et al, 2003; see also Owuamalam et al, 2022), and the results from controlled laboratory studies have yielded more definitive unsupportive evidence (e.g., Owuamalam & Spears, 2020;Owuamalam et al, 2017).…”
Section: Introductionmentioning
confidence: 99%